Memajukan UMKM Masyarakat Kelurahan Tanjung Raja Selatan ditinjau dari Manajemen dan Akuntansi - Nurul Hutami Ningsih (Universitas Muhammadiyah Palembang, 2025)
This community service activity aims to improve the capacity and performance of Micro, Small, and Medium Enterprises (MSMEs) in Tanjung Raja Selatan Village through an applied management and accounting approach. The main problems faced by MSMEs in this area include weak business planning, suboptimal resource management, and a lack of systematic financial record-keeping, which impacts competitiveness and business sustainability. The activity's implementation methods included outreach, training, direct mentoring, and case study-based evaluations of individual MSMEs. Training materials covered operational management, strategic planning, simple financial reporting, cost analysis, and the use of digital technology in business management. The activity's results demonstrated an increased understanding of management and accounting concepts among MSMEs, demonstrated by their ability to develop business plans, maintain more accurate financial records, and identify opportunities for increased efficiency and profitability. Overall, this activity positively impacted MSME development in Tanjung Raja Selatan Village by strengthening management and accounting as a foundation for sustainable community business advancement.